The glaciated valley landsystem of Morsárjökull, southeast Iceland - David J. A. Evans; Marek Ewertowski; Chris Orton (Journal of Maps, 2017)
A 1:4470 map of the Morsárjökull foreland, southern Iceland shows the spatial distribution of post Little Ice Age glacial sediment–landform associations pertaining to the operation of a typical active temperate outlet glacier of the south Vatnajökull ice cap. The map depicts an exemplar for the debris-charged glaciated valley landsystem, with characteristics further indicative of ‘uncovered alpine glaciers’, such as the uneven distribution of moraine volume, the localized appearance of a fluted subglacial bed and within-valley lateral moraine asymmetry. Such glaciers are characterized by strong glacier-climate coupling, because temporally and spatially sporadic rock avalanche-type medial moraines can only locally retard ablation. This morainic debris also has a short residence time in the glacier system due to its strong coupling with the proglacial fluvial system and resulting in efficient sediment transfer. Areas of more substantial latero-frontal moraine document phases of rock slope failure onto the snout and the passage of the debris to the ice margin.